Gastric Duplication: A Rare Cause of Massive Lower Gastrointestinal Haemorrhage, Chest Wall Mass, and Enterocutaneous Fistula. (30th August 2012) - Kesieme, Emeka B.; Dongo, Andrew E.; Osime, Clement O.; Olomu, Sylvia C.; Awe, Oluwafemi O.; Eze, Gerald I.; Eluehike, Sylvester U.
Abstract : Gastric duplications are uncommon developmental abnormality reported to present with different clinical scenarios. We present a 2-1/2-year-old Nigerian female who started having intermittent massive lower gastrointestinal haemorrhage at 5 months of age. She subsequently developed a lower chest wall mass and enterocutaneous fistula. She was found to have gastric duplication with fistulous communication with the descending colon, spleen, and lower chest wall. To the best of our knowledge, this is the first paper on gastric duplication resulting in intermittent massive lower gastrointestinal bleeding mainly from splenic capsular erosion and fistula and enterocutaneous fistula resulting from erosion of anterior abdominal wall. Gastric duplication is hence an important rare cause of intermittent massive lower gastrointestinal haemorrhage and spontaneous enterocutaneous fistula in the paediatric population.